Stochastic analysis of continuously reinforced concrete pavements - Leiva Villacorta, Fabricio (2025)
Continuously reinforced concrete pavements are rigid pavements that are reinforced with steel bars in the longitudinal direction and are built without transverse joints. In this type of pavements it is important to control crack spacing and width, as well as the stress level in the steel bars so that these parameters remain within a range that will ensure good pavement performance. Considering variability of material properties and slab thickness through a stochastic analysis may help optimize the design process and reduce uncertainty. The objectives of this study were to evaluate the design methodology for continuously reinforced concrete pavements using a probabilistic analysis and to evaluate the variability of the design parameters: crack spacing, crack width and steel stress. To accomplish these objectives, the variability of the material properties and slab thickness was included through the Monte Carlo simulation method for a case study.